Access services are human services: Collaborating to provide textbook access to students. Issue 2 (3rd April 2017) - McElroy, Kelly; Moore, Dan; Hilterbrand, Lori; Hindes, Nicole
ABSTRACT: Despite the clear negative impact of high textbook costs on students, limits—including space, funding, and policies—prevent many academic libraries from fully supporting textbook collections. Partnering with other campus units on textbook lending requires creative thinking but can provide students access to other services in addition to the books they need for class. This article describes a partnership between an academic library and a student services unit to provide support for a noncustodial textbook lending program.